(untitled) (KYAMC Journal, 2019)
Background: As a part of modern surgical procedure, laparoscopic mesh repair of inguinal hernia should be safe, effective and have a short period of convalescence. Objective: This study was designed to compare the outcome following inguinal hernia repair, performed by laparoscopic technique and open mesh Lichtenstein (tension-free) repair. Materials and Methods: This prospective quasi experimental study was carried out in the department of surgery, Bangabandhu Sheikh Mujib Medical University, for a period of twelve (12) months. Total thirty six patients of inguinal hernia were included in this study. Result: Mean (±SD) age was 38.17 (±8.64) years. Mean (±SD) time for unilateral inguinal hernias were 55.30 (±11.01) minute in open mesh repair where as 76.07 (±13.71) minute in laparoscopically. For bilateral inguinal hernia, mean (±SD) time for open mesh repair was 92.4 (±10.26) minute and 81.2 (±10.44) minute in laparoscopically Seroma formation was in 4 patients of open mesh repair where as 5 patients of laparoscopic mesh repair. Sixteen patients of laparoscopic mesh repair needed more anaesthetic narcotics 16 patients of laparoscopic mesh repair had return to work within two weeks of surgery whereas only 10 (55.6%) patients of open mesh repair had return to work during same period of time. Pain at surgical site and discomfort was more in open mesh repair. Conclusion: Laparoscopic mesh repair is better than open mesh repair of inguinal hernia. KYAMC Journal Vol. 10, No.-2, July 2019, Page 85-89